Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 1 - Section 1.3 - Operations on Real Numbers and Order of Operations - Exercise Set: 73



Work Step by Step

$\frac{(3-\sqrt 9)-(-5-1.3)}{-3}=\frac{(3-3)-(-(5+1.3))}{-3}=\frac{0-(-6.3)}{-3}=\frac{6.3}{-3}=-2.1$ We know that $\sqrt 9=3$, because $3^{2}=3\times3=9$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.